The effectiveness of the World Anti-Doping Agency: developing a framework for analysis. Issue 2 (3rd April 2019) - Houlihan, Barrie; Vidar Hanstad, Dag
ABSTRACT: Although there are a number of studies of the effectiveness of the global anti-doping regime less attention has been paid to the performance and effectiveness of the World Anti-Doping Agency (WADA) as the lead organisation within the policy regime. The aim of the paper is to design a framework for the analysis of WADA's performance and effectiveness and to utilise the framework to provide an assessment of the impact of the Agency within the broader policy regime. The framework identifies a series of structural and contextual dimensions. The structural factors analysed are: the formal competencies granted to the IO and the clarity of the IO mission; the degree of regime embeddedness and exclusivity; organisational cohesion and design; leadership quality; resource availability and stakeholder involvement. The main external or contextual factors are: scientific or technological developments; economic developments; position on the policy agenda and competing policy concerns; the cost/benefit of political support and public attitudes. It is argued that the analytical framework enables a rounded and effective assessment of the contribution of WADA to the global anti-doping regime. Specifically it allows an assessment of WADA to be made from two distinct perspectives: the first focuses on its performance and effectiveness in terms of the objectives that it has set for itself or which have been set for it by its principals while the second focuses on the performance of WADA in comparison with other similar IOs.